The Effectiveness of Learning Materials Based on Local Potentials on Students’ Interests and Learning Outcomes - Kholifahrini, Riska; Susilowati, Sri Mulyani Endang; Nugroho, Sunyoto Eko (Jurnal Profesi Keguruan, 2019)
This study aims to describe the effectiveness of learning materials based on local potentials on the improvement of students? interests and learning outcomes at SD N Malingmati II for Theme 1 ?Save Living Things.? The research sample was students of grade 6 SD N Malingmati as many as 34 students. The type of research that is used in this study is quasi-experimental research with one group pre-test ? post-test design. Data were descriptively analyzed. The techniques of data collection used pre-test and post-test, as well as questionnaires. The result of the study showed that learning materials based on local potentials were effective in improving students? learning outcomes. Students? learning outcomes had N-gain 0.72 which was in the high category. The result of questionnaires about students? interest in science learning based on local potentials was in the excellent criteria. The highest interest percentage was in the aspect of concern for local potentials as much as 92%. The lowest interest percentage of the length of learning science was 85% because the students were not only focused on science only, but also integrated thematic learning.